Analysis of thermophysical properties of asphalt mixtures - Zorin, V A; Baurova, N I; Kosenko, E A (IOP conference series. Materials Science and Engineering, 2020)
The article describes the main stages of experimental design of thermophysical properties of asphalt mixtures. Based on the results experimental studies, we have constructed graphs showing the dependence of the cooling time of the asphalt concrete mixture on environmental conditions and the method of thermal insulation of the asphalt concrete mixture during its transportation. Thermograms of experimental samples clearly show the effectiveness of various methods of thermal insulation of asphalt concrete mixes. The choice of a regression model characterizing the dependence of the cooling time of an asphalt concrete mix on variable factors is substantiated.